Analisis Faktor – Faktor yang Mempengaruhi IPM Jawa Timur dengan PDRB sebagai Variabel Moderasi - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research aims to determine the effect of Poverty Level and Open Unemployment Rate on the Human Development Index with Domestic Regional Domestic Income as a Moderating Variable. This research uses quantitative methods, the research population is 38 cities and regencies in East Java, the research sample comes from data for 2018 - 2022. Researchers use a data and document collection model from the Central Statistics Agency (BPS). The analysis process uses multiple regression analysis of panel data assisted by Eviews 12. The results of this research state that the Poverty Level and Open Unemployment Rate have a significant negative effect on HDI, and GRDP can moderate the relationship between Poverty Level, TPT and HDI